Improved Ambiguity-Resolving for Virtual Baseline - Hailiang Song; Yongqing Fu; Xue Liu (Universitas Ahmad Dahlan, 2014)
A novel phase interferometer method based on virtual baseline is proposed for technical difficulty in resolving angle ambiguity and antenna layout. In this method, only two baselines are set to solve the problem of angle ambiguity. In high noise areas, there are large numbers of outliers which lead to angle error in the measured data, and a way to detect and eliminate the outliers is applied to improve the effect of solving ambiguity. The simulation results show that the improved method could effectively correct the error of fuzzy phase difference and increase the probability of ambiguity-resolving. Duo to its simple equipment and easy to implement, the proposed method might have certain guiding significance to engineering application.